A conventional surgical approach for removal of an ectopic tooth in the nasal cavity. Issue 8 (2nd August 2019) - Gormley, Mark; Chahal, Ramanjot; Gallacher, Nicola; Bell, Christopher
Abstract : A 40-year-old female patient presented to ears, nose and throat complaining of cacosmia and discharge from the left maxillary sinus. Her CT scan revealed an ectopic supplemental nasal tooth which could not be removed by nasoendoscopy. Therefore, a conventional intraoral surgical approach was taken. In this case, we discuss the indications for conventional surgical removal of teeth from the nasal cavity when a nasoendoscopic approach is not possible. We highlight the potential pitfalls of both conventional and nasoendoscopic approaches, including some essential considerations when treatment planning these cases.